Maritime Academy Gets High Praise - Unknown (Unknown)
State Sen. Luther E. Gibson, Assemblyman Samuel R. Geddes and officials of the California Maritime Academy were singled out yesterday by Gov. Edmund G. (Pat) Brown for their role in helping the continued growth and success of California's own maritime school.